Efektivitas Implementasi Komunitas Belajar pada Satuan Pendidikan Anak Usia Dini Program Sekolah Penggerak - Rahman, Misran (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2025)
This research aims to evaluate the effectiveness of implementing learning communities in supporting the development of Early Childhood Education Units (PAUD) in the Driving School Program. Learning communities are a collaborative approach that aims to improve educator competence through discussion, reflection and joint learning. The research method used is descriptive qualitative with data collection techniques through surveys and interviews. Research subjects included educators and school principals in PAUD units of the Mobilizing School Program. The results of the research show that the learning community procedures have been implemented well by the PAUD unit of the driving school program. In addition, learning communities have played a significant role in improving several aspects of educators' professional learning competencies, including learning planning and designing learning evaluations. However, it has not played a significant role in the implementation of student-centred learning and differentiated learning. In conclusion, the implementation of learning communities in PAUD Units in the Driving School Program is generally effective in supporting improvements in the quality of early childhood education. Recommendations are provided to strengthen program sustainability through providing adequate resources and strengthening collaboration between stakeholder